Study of Comparison of Stock Performance Before And After Doing Split Stock In Go Public Companies That Are Listing on The Idx Period 2013 – 2015 - Yuniati, R.A. Norromadani; Agatha Putri, Mirza Safitri; Rabbani, Latof Syeikhur (Aptisi Transactions On Technopreneurship (ATT), 2020)
This study aims to determine the difference in abnormal return, trading volume activity, and security return variability before and after the stock split announcement on companies listed on the Indonesia Stock Exchange for the period 2013 - 2015. Testing the information content will be done by looking at differences in average abnormal return, average security return variability and average trading volume activity five days before and five days after the announcement of the stock split. The data analysis method that will be used is descriptive statistical analysis and different tests before and after the stock split announcement using the Wilcoxon signed rank test. The results of this study indicate that there are significant abnormal return differences before and after the stock split announcement, there is no significant difference in trading volume activity before and after the stock split announcement, and there is no significant difference in security return variability before and after the stock split announcement.